The Validity of a Simple Outcome Measure to Assess Stuttering Therapy - Huinck, Wendy; Rietveld, Toni (Folia phoniatrica et logopaedica, 2007)
Objective: The validity of a simple and not time-consuming self-assessment (SA) Scale was tested to establish progress after or during stuttering therapy. Patients and Method: The scores on the SA scale were related to (1) objective measures (percentage of stuttered syllables, and syllables per minute) and (2) (self-)evaluation tests (self-evaluation questionnaires and perceptual evaluations or judgments of disfluency, naturalness and comfort by naïve listeners). Data were collected from two groups of stutterers at four measurement times: pretherapy, posttherapy, 12 months after therapy and 24 months after therapy. The first group attended the Comprehensive Stuttering Program: an integrated program based on fluency shaping techniques, and the second group participated in a Dutch group therapy: the Doetinchem Method that focuses on emotions and cognitions related to stuttering. Results: Results showed similar score patterns on the SA scale, the self-evaluation questionnaires, the objective measures over time, and significant correlations between the SA scale and syllables per minute, percentage of stuttered syllables, Struggle subscale of the Perceptions of Stuttering Inventory and judged fluency on the T1-T2 difference scores. Conclusion: We concluded that the validity of the SA measure was proved and therefore encourage the use of such an instrument when (stuttering) treatment efficacy is studied.